Electrochemical Detection of Metronidazole by the Fabricated Composites of Orthorhombic Iron Tungsten Oxide Decorated with Carbon Nanofiber Composites Electrode. Issue 3 (1st March 2023) - Mariappan, Kiruthika; Alagarsamy, SaranVignesh; Chen, Shen-Ming; Sakthinathan, Subramanian
Abstract : Metronidazole (MTD) is a common antibiotic used to treat various pathogens and protozoal infections in humans and domestic animals. Anyhow, this drug is prohibited in various countries owing to its extremely precarious properties. Hence, the low-limit detection of MTD in the environment is more important because it is very impactful and affects human health. Iron tungstate (Fe2 WO6 ) has been produced by the hydrothermal method and the carbon nanofibers (CNF) prepared from the electrospinning technique. After that, CNF/Fe2 WO6 composite decorated glassy carbon electrode (GCE) was used for the electrochemical detection of MTD. Here, the different physicochemical characterization studies were used to confirm the CNF/Fe2 WO6 composite. Moreover, Electrochemical Impedance spectroscopy, cyclic voltammetry studies, and Differential pulse voltammetry have been used for the electrochemical studies of modified electrodes. The electrochemical results of GCE/CNF/Fe2 WO6 electrodes exhibited an excellent electrochemical response at −0.5 V. The MTD detection limit has been calculated by the very low detection limit concentrations (0.013 μ M). Further, the GCE/CNF/Fe2 WO6 electrodes performed at high sensitivity (1.55 μ A μ M −1 cm −2 ) with a wide linear range (0.01–1792 μ M). Besides, the GCE/CNF/Fe2 WO6 have excellent repeatability, reproducibility, stability, and real sample analysis performance.